The Effect of Servant Leadership on Employee Performance with Organizational Citizenship Behaviors as Intervening Variable Study Case at Bank BTPN Jakarta Head Office - Dicka Fadillah Putrawijaya; Sri Wahyu Lely Hana; Intan Nurul Awwaliyah (Budapest International Research and Critics University, 2022)
This study investigated the effect of servant leadership on employee performance with organizational citizenship behavior as an intervening variable at Bank BTPN Jakarta Head Office. The population of this study were permanent employees at Bank BTPN Jakarta Head Office. The total population of permanent employees at Bank BTPN Jakarta Head Office were 391, including all business lines with permanent employee status at Bank BTPN Jakarta Head Office. Sampling technique used proportional random sampling, there were 78 respondents. The methods of data collections were survey, literature review, and questionnaire. Data analysis used outer model analysis, inner model analysis, and line analysis. The result showed that servant leadership contributes to a significant impact on employee performance. The second research results obtained proved that servant leadership positively influences and significantly impacts organizational citizenship behavior. The third result showed that organizational citizenship behavior positively influence and significantly impact employee performance. Furthermore, the following result showed that servant leadership significantly impacts employee performance through organizational citizenship behavior.